THE EDUCATIONAL IMPACT OF CHILDHOOD DEPRESSION AND THE NEED OF EARLY IDENTIFICATION - Mamta Kumari; Anubhav Dubey; Vikram Kumar Sahu; James Yamoah; Richard Owusu Nyarko; Rosemond Owusu Nyarko; Josephine Abba Sackey; Francis Asante (The Bioscan, 2025)
Background: Ten to twenty percent of kids and teens have mental health issues. Attention deficits, cognitive problems, low motivation, and depression hinder academic progress. It's sometimes unclear how psychologists affect kids' mental development and what school therapies and prevention efforts work. Methods: The foundation of this brief statement is the systematic reviews, meta-analyses, and randomized and non-randomized controlled trials found through a selective search in the PubMed and Google Scholar databases—ScienceDirect, Elsevier, ResearchGate, and others. Results: Impulsive conduct, a lack of focus, and hyperactivity in the motor areas are the hallmarks of this disorder. Depression affects 4-5% of children and adolescents, with a double prevalence that of males compared to girls. Learning impairments, including dyslexia and dyscalculia, impact 4-6% of children. Repeated grades, chronic absenteeism, and dropping out of school are all associated with mental health issues. Incorporating evidence- based school programs and making adjustments to the school environment can reduce the likelihood of students developing internalizing or externalizing mental health problems. Conclusion: Doctors, school social workers, and psychologists must help educators identify and address mental health issues in their students to quickly identify school stressors and implement necessary interventions. School-entrance tests and risk factor testing can help. Schools must implement evidence-based preventative activities and enhance the school climate.